Carbon nanotube composite material and preparation method thereof

By adding carbon nanotubes, surfactant and white oil to the polymer, the carbon nanotube composite materials are formed, and the problems of insufficient conductivity and high cost in the prior art are solved, and the conductive performance improvement and mechanical performance are achieved. Suitable for anti-static and electromagnetic shielding.

CN119192722APending Publication Date: 2024-12-27YONGJIANG LAB
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411266476.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing polymer modification technology has problems such as insufficient conductivity, high cost and reduced mechanical properties in production and application. Especially when using carbon black as a conductive filler, it is necessary to add a lot to build a conductive network, resulting in the cost of composite materials and Poor performance.

Method used

Using 0.5-2 parts by mass of carbon nanotubes, 0.1-0.3 parts by mass of surfactant, 15-25 parts by mass of white oil and 75-99.5 parts by mass of polymer, the polymer was homogenized, distilled and blended. , form carbon nanotube composite materials, improve their conductivity and compatibility, and reduce the permeability threshold.

Benefits of technology

The conductive performance of carbon nanotube composites has been improved, the amount of conductive agent added is reduced, the mechanical properties of the polymer are maintained, and the cost is low, and the conductivity reaches 8×10-9S·cm-1×10-8S·cm , suitable as anti-static or electromagnetic shielding material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192722A_ABST
    Figure CN119192722A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanotube composite material and a preparation method thereof. The carbon nanotube composite material is prepared from the following components in parts by mass: 0.5 to 2 parts of carbon nanotube, 0.1 to 0.3 part of surfactant, 15 to 25 parts of white oil and 75 to 99.5 parts of polymer. By adding the carbon nanotubes into the polymer, the conductivity of the polymer is improved, and the polymer has good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of conductive polymer composite materials, in particular, to carbon nanotube composite materials and preparation methods thereof. Background Art

[0002] Polymers often have certain mechanical properties and excellent processing properties. Common general-purpose plastics, such as polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), etc., have huge annual output. They are widely used in life and industrial production because they are easy to process and light in weight. Polymers are widely used in packaging materials, electrical equipment, automotive parts and other fields because of their unique physical, chemical and mechanical properties. Because most polymers also have electrical insulation, in some usage scenarios, insulating polymers need to be modified. The modification method can be to add some conductive materials to make it have certain antistatic properties, or to add more conductive materials to make it have electromagnetic shielding effect. The current polymer modification scheme still has many problems in the actual production and application process. Summary of the invention

[0003] In a first aspect of the present application, a carbon nanotube composite material is proposed, comprising: 0.5 to 2 parts by mass of carbon nanotubes, 0.1 to 0.3 parts by mass of a surfactant, 15 to 25 parts by mass of white oil, and 75 to 99.5 parts by mass of a polymer.

[0004] Therefore, the carbon nanotube composite material proposed in the present application is a carbon nanotube composite material, and each component forms a good interface bond and does not undergo chemical reaction. By adding carbon nanotubes to a polymer, the conductive property of the polymer can be improved, and the polymer has good mechanical properties.

[0005] In some embodiments, the volume conductivity of the carbon nanotube composite material is 8×10 -9 S cm-1×10 - 8 S·cm.

[0006] In some embodiments, the carbon nanotubes include at least one of single-walled carbon nanotubes, few-walled carbon nanotubes, and multi-walled carbon nanotubes. Thus, the addition of carbon nanotubes improves the conductivity of the carbon nanotube composite material.

[0007] In some embodiments, the polymer includes at least one of polyethylene, polypropylene, and ethylene-vinyl acetate copolymer. Thus, the aforementioned polymer is used as a dispersion medium of the carbon nanotube composite material, and the obtained carbon nanotube composite material has good compatibility.

[0008] In some embodiments, the surfactant includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecyltrimethylammonium bromide, didodecyldimethylammonium bromide, sodium lignin sulfonate, alkali lignin, and sodium dodecyl sulfate.

[0009] The aforementioned surfactant can reduce the difference in surface tension between different components in the carbon nanotube composite material to improve the blending quality.

[0010] In some embodiments, the viscosity of the white oil is 5 cSt-180 cSt. Therefore, within the aforementioned viscosity range, the white oil can play a lubricating role and assist in uniform mixing of the components in the carbon nanotube composite material.

[0011] In the second aspect of the present application, the present application proposes a method for preparing a carbon nanotube composite material, comprising: homogenizing carbon nanotubes, an alcohol solvent, and a surfactant to obtain a carbon nanotube slurry; mixing the carbon nanotube slurry with white oil and performing a distillation process to obtain a carbon nanotube oil; and blending the carbon nanotube oil with a polymer to obtain the carbon nanotube composite material. Thus, by adding and mixing the alcohol solvent, the surfactant, and the white oil at different stages, the compatibility of the incompatible components can be improved, so that the prepared carbon nanotube composite material has a network of interwoven components of the blended components, thereby achieving modification of the polymer.

[0012] In some embodiments, in the carbon nanotube slurry, the mass ratio of the carbon nanotubes, the alcohol solvent, and the surfactant is (0.5-3):(90-110):(0.1-0.6).

[0013] In some embodiments, the mixing mass ratio of the carbon nanotube slurry and the white oil is (0.5-5): 1. Thus, when the components in the carbon nanotube slurry and the carbon nanotube slurry and the white oil are mixed in the aforementioned mass ratio, the carbon nanotubes can be fully dispersed and stretched, which is beneficial for further blending treatment.

[0014] In some embodiments, the blending mass ratio of the white oil to the polymer is (5-35):(80-120). Thus, the mass ratio of the white oil to the polymer in the carbon nanotube composite material is within the aforementioned range, which can achieve good compatibility.

[0015] In some embodiments, the alcohol solvent includes at least one of methanol, ethanol, and isopropanol. Thus, the alcohol solvent does not react with the carbon nanotubes or the surfactant.

[0016] In some embodiments, the pressure of the homogenization treatment is 5000psi-25000psi, and the number of cycles of the homogenization treatment is 2 times-4 times. After the above-mentioned homogenization treatment pressure conditions and number of cycles, the agglomerated morphology of the carbon nanotubes can be arranged and expanded, which is conducive to further forming a network structure in the carbon nanotube composite material.

[0017] In some embodiments, the distillation temperature is 50°C-90°C.

[0018] In some embodiments, the vacuum degree of the distillation process is 0.05 MPa-0.1 MPa.

[0019] Under the temperature and vacuum conditions of the aforementioned distillation treatment, the alcohol solvent in the carbon nanotube slurry can be evaporated and removed.

[0020] In some embodiments, the blending process includes at least one of melt blending and mechanical blending. By the aforementioned method, the components are fully blended, and the carbon nanotubes and the polymer form a mixed network structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0022] Figure 1 This is a schematic diagram of the structure of multiple carbon nanotubes in one embodiment of the present application;

[0023] Figure 2 This is a SEM (scanning electron microscope) image of a carbon nanotube composite material according to an embodiment of the present application;

[0024] Figure 3 This is a SEM image of a carbon nanotube composite material according to an embodiment of the present application;

[0025] Figure 4 The present invention is a flow chart of a method for preparing a carbon nanotube composite material in one embodiment of the present invention. DETAILED DESCRIPTION

[0026] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0027] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0028] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0029] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.

[0030] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0033] Conductive fillers that can be added to polymer materials for polymer modification include metallic conductive fillers and non-metallic conductive fillers. Among non-metallic conductive fillers, carbon materials are the most widely used, including carbon black, graphene, carbon fiber, carbon nanotubes, etc. Among them, carbon black is the most widely used due to its low price. However, carbon black is mostly spherical and mixed in polymer materials. Its conductive process is mostly point contact, and the percolation threshold is high. If carbon black is to build a conductive network in the polymer, a large amount of addition is required, which will greatly reduce the mechanical properties of the polymer material and increase the cost of the composite material. With the increase in the production of carbon nanotubes, especially multi-walled carbon nanotubes, and the substantial reduction in prices, carbon nanotubes can be used as conductive fillers in large quantities in the field of conductive polymer composite materials. Unlike the spherical shape of carbon black, carbon nanotubes are a one-dimensional linear structural material that can build a mesh conductive structure in polymer materials. Its percolation threshold is much smaller than that of carbon black materials. Therefore, in the field of conductive plastics, carbon nanotube materials are gradually replacing carbon black.

[0034] However, due to the strong van der Waals forces between carbon nanotubes, carbon nanotubes often appear in the form of array agglomerates. When nanotubes are blended with polymer materials, in order to achieve a better blending effect, the carbon nanotubes need to be dispersed as much as possible into a single state, so as to achieve the purpose of building a conductive network with the smallest amount of addition. When polymers and carbon nanotubes are melt blended as conductive fillers, due to the influence of the van der Waals forces between carbon nanotubes, the percolation threshold of carbon nanotubes as conductive fillers is still relatively large, and the cost of preparing conductive composite materials is high.

[0035] In a first aspect of the present application, a carbon nanotube composite material is proposed, comprising: 0.5 to 2 parts by mass of carbon nanotubes, 0.1 to 0.3 parts by mass of a surfactant, 15 to 25 parts by mass of white oil, and 75 to 99.5 parts by mass of a polymer.

[0036] The carbon nanotube material has conductive properties. After being fully blended with the polymer, the insulating polymer itself has certain conductive properties. The carbon nanotube composite material can play a certain role in antistatic or electromagnetic shielding as a shell material or packaging material. When the amount of carbon nanotubes added is within the aforementioned range, the mechanical properties of the polymer as the substrate can still be well maintained. When the carbon nanotubes are added in the same proportion, the better the mixing compatibility of the carbon nanotubes and the polymer material, the greater the improvement of the conductive properties of the carbon nanotube composite material by the carbon nanotubes.

[0037] In some embodiments, the volume conductivity of the carbon nanotube composite material is 8×10 -9 S cm-1×10 - 8 S·cm.

[0038] refer to Figure 2 and Figure 3 In the carbon nanotube composite material proposed in this application, the carbon nanotubes are fully dispersed, the carbon nanotubes and the polymer are well compatible, the percolation threshold is reduced, and the conductivity of the carbon nanotube composite material can reach 8×10 - 9 S cm-1×10 -8 S·cm.

[0039] In some embodiments, the carbon nanotubes include at least one of single-walled carbon nanotubes, few-walled carbon nanotubes, and multi-walled carbon nanotubes.

[0040] refer to Figure 1 Carbon nanotubes are one-dimensional tubular materials. The carbon-carbon bonds inside carbon nanotubes are similar to sp 2 The hybrid structure has excellent mechanical and electrical properties. Among them, multi-walled carbon nanotubes can be regarded as multiple layers (more than 10 layers) of single-walled carbon nanotubes rolled up, and oligo-walled carbon nanotubes can be carbon nanotubes with 3-8 layers of tube walls.

[0041] In some embodiments, the polymer includes at least one of polyethylene, polypropylene, and ethylene vinyl acetate copolymer.

[0042] In the carbon nanotube composite material proposed in the present application, the aforementioned polymer is used as a base material, which can be well mixed with various components in the blending system.

[0043] In some embodiments, the surfactant includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecyltrimethylammonium bromide, didodecyldimethylammonium bromide, sodium lignin sulfonate, alkali lignin, and sodium dodecyl sulfate.

[0044] The aforementioned surfactant can wet the surface of the components in the blending system to promote the compatibility of the carbon nanotubes and the polymer.

[0045] In some embodiments, the viscosity of the white oil is 5 cSt-180 cSt.

[0046] When the white oil is within the aforementioned viscosity range, the selected white oil is a liquid with strong fluidity, such as No. 5 white oil. White oil is mainly composed of hydrocarbons, and its main components are aromatic hydrocarbons and aliphatic hydrocarbons. White oil is basically immiscible with the alcohol solvent and does not undergo chemical reaction, but has good compatibility with the polymer.

[0047] In the second aspect of the present application, the present application proposes a method for preparing a carbon nanotube composite material, comprising: homogenizing carbon nanotubes, an alcohol solvent, and a surfactant to obtain a carbon nanotube slurry; mixing the carbon nanotube slurry and white oil, and distilling the mixture to obtain a carbon nanotube oil; and blending the carbon nanotube oil with a polymer to obtain the carbon nanotube composite material.

[0048] Carbon nanotube materials have a large aspect ratio. Generally, most carbon nanotubes are in a state of aggregation, which will further increase the resistance to the blending of carbon nanotubes and polymers. Figure 4 , dispersing carbon nanotubes in a cheap alcohol solvent to obtain a highly dispersed carbon nanotube slurry. Then, the carbon nanotubes are dispersed in the alcohol solvent by homogenization to open the agglomerated structure. Because the polarity difference between the polymer and the alcohol solvent is large, while the polarity difference between the white oil and the polymer is small, further, by adding white oil and removing the alcohol solvent, the monodispersed carbon nanotubes are dispersed in the white oil. Since the viscosity of white oil is high at room temperature, the fluidity of white oil is strong at a temperature of 60°C-80°C. After the carbon nanotube slurry is mixed with the white oil and then distilled, it is beneficial to fully mix the white oil and the carbon nanotube slurry. Afterwards, the carbon nanotubes fully dispersed in the white oil are blended with the polymer, which is beneficial to form a conductive network constructed by the monodispersed state of the carbon nanotubes when blended with the polymer.

[0049] In some embodiments, in the carbon nanotube slurry, the mass ratio of the carbon nanotubes, the alcohol solvent, and the surfactant is (0.5-3):(90-110):(0.1-0.6).

[0050] In some embodiments, the mixing mass ratio of the carbon nanotube slurry and the white oil is (0.5-5):1.

[0051] In some embodiments, the blending mass ratio of the white oil and the polymer is (5-35):(80-120).

[0052] In the carbon nanotube slurry, the carbon nanotubes, the alcohol solvent, and the surfactant are mixed in the aforementioned mass ratio, and the carbon nanotubes can have enough space to disperse in the alcohol solvent. The carbon nanotubes are pre-dispersed by the alcohol solvent and then blended with the white oil. The solution obtained by blending has good fluidity and is conducive to homogenization in a homogenizer, so that the carbon nanotubes can be evenly dispersed therein. The carbon nanotube slurry and the white oil are mixed in the aforementioned mass ratio, which is conducive to the carbon nanotubes remaining in a monodisperse state after being mixed with the white oil and removing the alcohol solvent. White oil is also a component for polymer modification, which can reduce the cost of carbon nanotube composite materials and also play a role in toughening. The appropriate amount of carbon nanotubes added makes the stress generated by the prepared carbon nanotube composite material relatively dispersed when there is an external force, and can maintain the mechanical properties of the carbon nanotube composite material.

[0053] In some embodiments, the alcohol solvent includes at least one of methanol, ethanol, and isopropanol.

[0054] The alcohol solvent does not react with the carbon nanotubes or surfactants, and the alcohol solvent has a low boiling point, which is conducive to distillation treatment in a relatively stable temperature range. Its boiling point is also different to a certain extent, which is conducive to the recycling and reuse of the alcohol solvent.

[0055] In some embodiments, the alcohol solvent is methanol, ethanol, isopropanol, or a mixture of the three in any ratio.

[0056] In some embodiments, the pressure of the homogenization treatment is 5000psi-25000psi, and the number of cycles of the homogenization treatment is 2-4 times.

[0057] Within the aforementioned pressure range of the homogenization treatment, the homogenization treatment can disperse the agglomerated carbon nanotubes without destroying or affecting the structure of the carbon nanotubes themselves, which is beneficial to further forming a conductive network structure in the carbon nanotube composite material.

[0058] In some embodiments, the temperature of the distillation treatment is 50°C-90°C; and / or the vacuum degree of the distillation treatment is 0.05MPa-0.1MPa.

[0059] Within the aforementioned distillation temperature range, the alcohol solvent can be removed, and the physical and chemical properties of each component in the blend system are less affected. Distillation within the aforementioned vacuum range can accelerate the removal of the alcohol solvent, which is beneficial to reducing the preparation time of the carbon nanotube composite material.

[0060] In some embodiments, the blending process includes at least one of melt blending and mechanical blending.

[0061] In some embodiments, the blending process is a twin-screw extruder blending extrusion.

[0062] In some embodiments, the twin-screw extruder has a rotation speed of 130 rpm-200 rpm.

[0063] In some embodiments, the temperature of each area of ​​the twin-screw extruder from the feed port to the die head can be adjusted according to the type of polymer.

[0064] In some embodiments, the temperature of the twin-screw extruder from the feed port to the head area can be adjusted according to the type of polymer.

[0065] In some embodiments, the temperatures of the six zones of the twin-screw extruder from the feed port to the die are controlled at 135°C, 165°C, 175°C, 180°C, 175°C, and 170°C, respectively.

[0066] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0067] Example 1

[0068] Step 1: Weigh each component material, measure by mass, 1.5 parts of multi-walled carbon nanotubes, 100 parts of ethanol solvent, and 0.3 parts of sodium lignin sulfonate, add them into a homogenizer for homogenization, and obtain carbon nanotube slurry after 3 cycles under a pressure of 8000 psi;

[0069] Step 2: Evenly mix the carbon nanotube slurry obtained in step 1 with white oil, wherein the mass ratio of the carbon nanotube slurry to the white oil is 2:1, and then evaporate the solvent from the solution at 85° C. using a rotary evaporation process to recover the solvent, and the vacuum degree of the rotary evaporation process is 0.1 MPa, to obtain carbon nanotube oil;

[0070] Step 3: 20 parts of the carbon nanotube oil obtained in step 2 and 80 parts of polypropylene are blended and extruded in a twin-screw extruder to obtain a product. The process parameters of the twin-screw extruder are: rotation speed 180 rpm, and the temperature control of the six zones from the feed port to the head are 135°C, 165°C, 175°C, 180°C, 175°C, and 170°C respectively.

[0071] Example 2

[0072] Example 2 is consistent with Example 1, except that in step 1, the weight parts of each component are: 2 parts of multi-walled carbon nanotubes, 100 parts of ethanol solvent, and 0.4 parts of sodium lignin sulfonate.

[0073] Example 3

[0074] Example 3 is consistent with Example 1, except that in step 1, the weight parts of each component are: 2 parts of multi-walled carbon nanotubes, 100 parts of methanol solvent, and 0.4 parts of sodium lignin sulfonate.

[0075] Comparative Example 1

[0076] Blending extrusion: 0.6 parts of carbon nanotubes and 100 parts of polypropylene were blended in a twin-screw extruder to obtain the product. The process parameters of the twin-screw extruder were: rotation speed 200 rpm, and the temperature control of the six zones from the feed port to the die head were 135°C, 165°C, 175°C, 180°C, 175°C, and 170°C respectively.

[0077] Comparative Example 2

[0078] Comparative Example 2 is consistent with Comparative Example 1, except that the weight parts of each component are: 2 parts of carbon nanotubes and 100 parts of polypropylene.

[0079] Comparative Example 3

[0080] Co-blending extrusion: 0.6 parts of carbon nanotubes, 20 parts of white oil (viscosity 15 cSt), and 80 parts of polypropylene were co-blended in a twin-screw extruder to obtain the product. The process parameters of the twin-screw extruder were: rotation speed 180 rpm, and the temperature control of the six zones from the feed port to the die head were 135°C, 165°C, 175°C, 180°C, 175°C, and 170°C, respectively.

[0081] Comparative Example 4

[0082] Comparative Example 4 is consistent with Comparative Example 3, except that the weight parts of each component are: 2 parts of carbon nanotubes, 20 parts of white oil (viscosity 15 cSt), and 80 parts of polypropylene.

[0083] Comparative Example 5

[0084] Comparative Example 5 is consistent with Comparative Example 3, except that the weight parts of each component are: 4 parts of carbon nanotubes, 20 parts of white oil (viscosity 15 cSt), and 80 parts of polypropylene.

[0085] Test method: The electrical and mechanical properties of the above comparative examples and embodiments were tested.

[0086] Mechanical properties test: GB / T1040.2 standard test method to test tensile strength and elongation at break,

[0087] Electrical performance test: The volume conductivity of the carbon nanotube composite material was tested using the standard experimental method in ASTM D257.

[0088] Test results: The performance test results of carbon nanotube composite materials are shown in Table 1

[0089] Table 1

[0090]

[0091] The following analysis and conclusions can be drawn from the test results in Table 1:

[0092] 1. Taking polypropylene as an example, the tensile strength of pure polypropylene is 24MPa-25MPa, and the elongation at break is about 250%. From the test results, it can be seen that adding a certain amount of carbon nanotubes can improve the tensile strength of the material to a certain extent, but adding too much carbon nanotubes will cause carbon nanotube aggregation, which will cause material stress concentration under the application of external force, and reduce the mechanical properties of the material. The addition of white oil can improve the elongation at break of the material, but it will greatly reduce the tensile strength of the material. From the perspective of volume conductivity, white oil can improve the dispersion of carbon nanotubes in polypropylene to a certain extent and improve the conductive properties of the material.

[0093] 2. The method of the present application can effectively disperse carbon nanotubes in polypropylene, thereby greatly improving the conductivity of the prepared carbon nanotube composite material. From the perspective of volume conductivity, the conductivity of the material can be increased by 1-2 orders of magnitude.

[0094] 3. Adding carbon nanotube conductive agent within a certain range can further improve the conductivity of the material.

[0095] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0096] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0097] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A carbon nanotube composite material, characterized in that: include: 0.5 to 2 parts by mass of carbon nanotubes, 0.1 to 0.3 parts by mass of a surfactant, 15 to 25 parts by mass of white oil, and 75 to 99.5 parts by mass of a polymer.

2. The carbon nanotube composite material according to claim 1, characterized in that: The carbon nanotubes include at least one of single-walled carbon nanotubes, few-walled carbon nanotubes, and multi-walled carbon nanotubes.

3. The carbon nanotube composite material according to claim 1, characterized in that: The polymer includes at least one of polyethylene, polypropylene, and ethylene-vinyl acetate copolymer; and / or, The surfactant includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecyltrimethylammonium bromide, didodecyldimethylammonium bromide, sodium lignin sulfonate, alkali lignin, and sodium dodecyl sulfate.

4. The carbon nanotube composite material according to claim 1, characterized in that: The viscosity of the white oil is 5 cSt-180 cSt.

5. A method for preparing the carbon nanotube composite material according to any one of claims 1 to 4, characterized in that: include: homogenizing the carbon nanotubes, the alcohol solvent, and the surfactant to obtain a carbon nanotube slurry; The carbon nanotube slurry is mixed with white oil, and subjected to distillation treatment to obtain carbon nanotube oil; The carbon nanotube oil is blended with a polymer to obtain the carbon nanotube composite material.

6. The method according to claim 5, characterized in that In the carbon nanotube slurry, the mass ratio of the carbon nanotubes, the alcohol solvent, and the surfactant is (0.5-3):(90-110):(0.1-0.6); and / or, The mixing mass ratio of the carbon nanotube slurry to the white oil is (0.5-5):1; and / or, The blending mass ratio of the carbon nanotube oil and the polymer is (5-35):(80-120).

7. The method according to claim 5, characterized in that The alcohol solvent includes at least one of methanol, ethanol and isopropanol.

8. The method according to claim 5, characterized in that The pressure of the homogenization treatment is 5000psi-25000psi, and the number of cycles of the homogenization treatment is 2 times-4 times.

9. The method according to claim 5, characterized in that The distillation temperature is 50°C-90°C; and / or, The vacuum degree of the distillation treatment is 0.05MPa-0.1MPa.

10. The method according to claim 5, characterized in that The blending process includes at least one of melt blending and mechanical blending.

Citation Information

Patent Citations

  • Carbon nanotube / polyolefin conductive composite material and preparation method

    CN102952328A

  • Graphene / carbon nanotube synergistic modified PVC (Polyvinyl Chloride) composite material as well as preparation method and application thereof

    CN107129643A

  • Easy-to-disperse carbon nanotube master batch as well as preparation method and application thereof

    CN111171430A

  • Carbon nanotube conductive masterbatch and preparation method thereof

    CN111363220A

  • Obtaining pulverulent compositions, useful as polymeric materials, reinforcement and / or modifying agent, comprises contact of carbon nanotubes e.g. with a monomer (mixture), optional heat treatment, purification and / or separation

    FR2893946A1